A rereading of Semblanzas (satire and politics of Ricardo Palma) - Kapsoli Escudero, Wilfredo (2023)
Ricardo Palma is the creator of the literary genre known as Las Tradiciones, which are short stories with the purpose of spreading a Smiling History of Peru from the world of the Incas to the republican society. Although he did not develop it extensively, he has also left us satirical epigrams dedicated to parliamentarians and government authorities of the country. In fact, the importance of this creation was made known by our teacher Alberto Tauro del Pino with a prologue to this literary creation, which we support with a new reading of the paper mentioned. Keywords: Tradition, portraits, epigram, satire, deputy.